A mixed-valent vanadium oxide cathode with ultrahigh rate capability for aqueous zinc-ion batteries. Issue 39 (27th September 2021) - Li, Shenglong; Wei, Xiujuan; Chen, Haopeng; Lai, Guoyong; Wang, Xuanpeng; Zhang, Shaojian; Wu, Shuxing; Tang, Weiting; Lin, Zhan
Abstract : The V10 O24 · n H2 O cathode with a large interlayer spacing and stable structure exhibits superior rate capability and excellent cycling stability for aqueous zinc-ion batteries. Abstract : The development of high-performance cathode materials is the key to realize commercial applications of zinc-ion batteries (ZIBs). Vanadium-based materials have been used as cathode candidates for ZIBs due to their low cost and high capacity. However, the low conductivity, unstable layered structure and slow diffusion kinetics of Zn 2+ are still the main problems for vanadium-based oxides. Herein, V10 O24 · n H2 O with a large interlayer spacing and stable structure is successfully synthesized by inducing a VO2 phase transition through a simple refluxing process. As the ZIB cathode material, V10 O24 · n H2 O demonstrates a high reversible capacity of 365.3 mA h g −1 at 0.2 A g −1, ultrahigh rate performance (127.2 mA h g −1 even at 80 A g −1 ), and long-term cycling stability (83.2% capacity retention over 3000 cycles at 5.0 A g −1 ). The excellent electrochemical performance is attributed to the synergistic effects of the ultrathin nanoribbon structures, oxygen vacancy and water molecules, which are favorable for enhancing the electron/ion transfer kinetics and maintaining structural stability of the V10 O24 · n H2 O electrode in the whole cycling process. Furthermore, ex situ XRD and XPS analyses elucidate the Zn 2+ storage mechanism of the V10 O24 · n H2 O cathode.